Post-Devolution Household Healthcare Expenditures in Rural Kenya - Omae, Peter Kabuka (European Scientific Journal, ESJ, 2024)
Introduction: Despite a country’s income improving in the era of decentralization, it does not obviously eliminate catastrophic expenditures. The study was conducted with an objective of establishing determinants of household expenditures in rural Kenya. Methods: The study made use of the Kenya Household Health Expenditure and Utilization Survey (2018) dataset. A multiple regression model was used to estimate the impact of respective determinants on post devolution health expenditures in rural Kenya. Ordinary Least Square (OLS) estimation technique was adopted in estimation. Results: Gender of the respondents, marital status, medical insurance and chronic illness were found to be positively related to health expenditure whereas education levels (primary, secondary and higher levels), wealth index (second and third wealth quintiles) were found to be significant predictors but had a negative relationship with health expenditures. Recommendations: The study suggests equality between men and women when it comes to health seeking and the use of incentives as well as training on men to practice preventive care so as to reduce costs going into hospitals for treatment unlike their female counterparts. Similarly, the study recommends for creation and implementation of awareness programmes and share across organizations, schools or government agencies. There is need to create empowerment programmes for the population so that they lower hospital visits and consequently lower health expenditures. There is also a need for the government to provide more public health facilities to boost or facilitate more use of subsidized services in rural areas.